Baseline carotid intima‐media thickness is associated with cardiovascular morbidity and mortality in peritoneal dialysis patients. Issue 6 (16th March 2021) - Asicioglu, Ebru; Velioglu, Arzu; Arikan, Hakki; Koc, Mehmet; Tuglular, Serhan; Ozener, Cetin
Abstract: Carotid intima‐media thickness (CIMT) is an early marker of atherosclerosis and is increased in peritoneal dialysis (PD) patients. Association of CIMT with cardiovascular disease (CVD) or mortality is less clear. Fibroblast growth factor‐23 (FGF‐23) is a hormone associated with vascular calcification, atherosclerosis, and mortality in the hemodialysis population. We investigated whether baseline CIMT and FGF‐23 are associated with CVD and mortality in PD patients. Fifty‐five PD patients were included. CVD was defined as ischemic heart disease, stroke, or peripheral artery disease. Intact FGF‐23 was measured in plasma. CIMT was measured by ultrasonography. Twenty‐one patients developed CVD and 12 died over 47.1 ± 33.8 months. Patients with CVD were older (55.9 ± 10.5 vs. 42.5 ± 12.9 years, P < .01), had lower albumin (3.8 ± 0.5 vs. 4.2 ± 0.3 g/dL, P < .01) and higher CIMT (0.87 ± 0.22 vs. 0.61 ± 0.11 mm, P < .01). Patients with mortality were also older (53.5 ± 11.5 vs. 45.8 ± 13.8 years, P = .05), had lower albumin (3.7 ± 0.6 vs. 4.1 ± 0.3 g/dL, P < .01), higher CRP (15.0 ± 8.5 vs. 7.6 ± 8.4 mg/L, P < .01) and CIMT (0.9 ± 0.3 vs. 0.6 ± 0.1 mm, P < .01). Albumin and CIMT were associated with CVD and CIMT > 0.75 mm was associated with cardiovascular mortality. FGF‐23 did not show any correlations. CIMT at baseline is associated with CVD and mortality in PD patients.